Mapping Research on Sovereign Bonds: A Bibliometric Analysis of Emerging Market Economies - Judijanto, Loso; Marjuki, Marjuki; Primasari, Niken Savitri (Westscience Press, 2025)
This study employs bibliometric analysis to map the scholarly landscape of sovereign bond research, focusing on the themes, geographic distribution, and evolution of the discourse from traditional financial analyses to contemporary issues like sustainability. Utilizing data from prominent academic databases, the research identifies key nodes and linkages within the global network of sovereign bond studies, highlighting the central roles of the United States and the United Kingdom, alongside the growing influence of emerging markets such as China and India. The analysis reveals a significant shift in research focus towards sustainability and green bonds, reflecting broader trends in global finance towards responsible investing. The study underscores the importance of interdisciplinary collaboration and the integration of diverse perspectives from both developed and developing nations to enhance the understanding and management of global financial systems.